Flashcard as A Teaching Aid: An Action Research on Vocabulary Measurement of EFL Students In SMK IP YADARO Moyot - Bayu Islam Assasaki (Institute of Educational, Research, and Community Service, 2024)
Indonesian education is in an adaptation process because the curriculum is changing from K- 13 to Curriculum Merdeka. Good techniques to teach kids to learn English must be a difficult task for the English teacher, especially adding new vocabulary every meeting. Therefore, this research was action research aimed to help students master the vocabulary in SMK IP YADARO Moyot, East Lombok. There were 15 students as samples in 1st grade. Collecting data using the form of vocabulary achievement tests filled during the action phase. The mean score pretest was 30, cycle 1 was 60 and cycle 2 was 80. This result indicated the use of flashcards effectively helped the students master the vocabulary beyond the minimum score target (70). The flashcard is colorful, bright, easy to carry, illustrative, and matches many activities and games.